2020
DOI: 10.3390/s20051525
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Fully Integrated Inductive Coupling System: A Discrete Approach Towards Sensing Ventricular Pressure

Abstract: In this paper, an alternative strategy for the design of a bidirectional inductive power transfer (IPT) module, intended for the continuous monitoring of cardiac pressure, is presented. This new integrated implantable medical device (IMD) was designed including a precise ventricular pressure sensor, where the available implanting room is restricted to a 1.8 × 1.8 cm2 area. This work considers a robust magnetic coupling between an external reading coil and the implantable module: a three-dimensional inductor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In inductive coupling, a magnetic field between two coils is utilized to carry information [93]. For example, for a micrometric coil system, the expected resonant frequency is in the order of hundreds of MHz [94]. In capacitive coupling, the electric field between two conductors or electrodes is utilized for the exchange of information.…”
Section: Non-radiative Technologiesmentioning
confidence: 99%
“…In inductive coupling, a magnetic field between two coils is utilized to carry information [93]. For example, for a micrometric coil system, the expected resonant frequency is in the order of hundreds of MHz [94]. In capacitive coupling, the electric field between two conductors or electrodes is utilized for the exchange of information.…”
Section: Non-radiative Technologiesmentioning
confidence: 99%
“…A novel attitude suggested by Sebastian et al. [110], depending on using bidirectional IC‐WPT to implement an integrated system to obtain continuous observation of cardiac pressure. The design (based on an RCL modelling circuit) works at 13.56 MHz resonance tuning.…”
Section: Previous Work On Near‐field Wireless Power Transfermentioning
confidence: 99%
“…The simulation result shows that the transmission efficiency remains stable even if the alignment between the transmitter and the receiver changes. A novel attitude suggested by Sebastian et al [110], depending on using bidirectional IC-WPT to implement an integrated system to obtain continuous observation of cardiac pressure. The design (based on an RCL modelling circuit) works at 13.56 MHz resonance tuning.…”
Section: Electrocardiograph Heart Rate and Cardiac Pressure Sensorsmentioning
confidence: 99%
“…To improve the performance of the WPT system (i.e. achieve maximum power and transfer efficiency) for IBMDs, numerous studies have reported different techniques, such as developing novel system topologies [16,17], proposing novel types of transmitting and receiving coils [15,18], improving misalignment conditions [19], and using various frequencies [7]. Delivering power wirelessly is only one part of the IBMD design.…”
Section: Introductionmentioning
confidence: 99%